Enterprise integration and information architecture : a systems perspective on industrial information integration - Xu, Li Da (Boca Raton : Auerbach Publications, 2015)
'This book provides a detailed description of enterprise information integration, from the development of enterprise systems for individual enterprises, to the extended enterprise information integration in supply chain environment, through discussing enterprise architecture, information architecture for enterprises, business process/work flow modeling, and enterprise information integration. The author clearly explains how industrial information integration can be more successful through the integration of systems approach as well as how systems science will profoundly impact and change the research in industrial information integration.'--
Includes bibliographical references and index.
Keywords: Management information systems; Business enterprises -- Computer networks; Software architecture